Adding MRI as a Surveillance Test for Hepatocellular Carcinoma in Patients with Liver Cirrhosis Can Improve Prognosis - Su Jong Yu; Jeong-Ju Yoo; Dong Ho Lee; Su Jin Kim; Eun Ju Cho; Se Hyung Kim; Jeong-Hoon Lee; Yoon Jun Kim; Jeong Min Lee; Jae Young Lee; Jung-Hwan Yoon (Biomedicines, 2023)
Gadoxetic acid disodium (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) can detect early stages of hepatocellular carcinoma (HCC). However, the survival benefit of Gd-EOB-DTPA-enhanced MRI in the surveillance of patients with cirrhosis has not yet been determined. We explored whether the intermittent replacement of ultrasonography (USG) with Gd-EOB-DTPA-enhanced MRI during HCC surveillance improved the clinical outcomes of patients with cirrhosis. We performed a retrospective cohort study of 421 HCC patients who were newly diagnosed during surveillance. Of these patients, 126 (29.9%) underwent surveillance based on Gd-EOB-DTPA-enhanced MRI and USG (USG+MRI group). The patients (295, 70.1%) who did not undergo MRI during surveillance were referred to as the USG group. In the USG+MRI group, 120 (95.2%) of 126 patients were diagnosed with early-stage HCC, whereas 247 (83.7%) of 295 patients were diagnosed with early-stage HCC in the USG group (P = 0.009). The significantly longer overall survival and time to progression in patients in the USG+MRI group compared to the unmatched cohort USG group was consistently observed by inverse probability weighting and propensity score-matched analysis. Gd-EOB-DTPA-enhanced MRI combined surveillance improved the detection of early-stage HCC and clinical outcomes such as overall survival and the time to progression in patients with cirrhosis.